Evaluating adherence to recommended clinical guidelines for the prevention of cardiovascular disease in patients with Type 2 diabetes mellitus at primary care level - Langenhoven, William (Department of Public Health and Family Medicine, 2017)
Background: Globally, type 2 diabetes (T2D) is a significant cause of avoidable mortality and morbidity. It is a major risk factor for cardiovascular disease (CVD). Evidence-based guidelines lower cardiovascular risk in diabetics. Adherence to clinical guidelines for the prevention of CVD in South African primary care public sector facilities is unknown. Aim: This study determined adherence of Cape Town primary care clinicians to recommended clinical guidelines for the prevention of cardiovascular disease in T2D. Methods: This 2013 cross-sectional study extracted data from 300 folders of known T2D patients sampled from three Community Health Centres (CHCs). Compliance with guidelines, and patient demographic factors were analysed. Results: Most (71% or 194/273) hypertensive diabetics were appropriately managed with first-line- medication - an Angiotensin Converting Enzyme Inhibitor (ACEI). There was appropriate supporting documentation for only 39% not on first line therapy. A fifth (22%) with drug intolerance received the recommended alternative. Most were appropriately prescribed a statin (74%) and aspirin (69%). Other cardiovascular risk factors were poorly controlled: mean weights were in the obese range (BMI=31.3 [SD: 5.7]); the mean total cholesterol level was 5.5 (SD: 1.4); there was incomplete data for smoking (19% had no record) and 93% had no record of a family history of CVD. Conclusions: Whilst pharmacological interventions for the prevention of CVD were moderately implemented, patient factors – such as obesity and smoking were poorly addressed. Improving documentation, adherence to recommended clinical guidelines and, health promotion to address modifiable risks are required to improve quality of care for T2D.